2022
DOI: 10.1155/2022/4869363
|View full text |Cite
|
Sign up to set email alerts
|

Forest Ecological Diversity Change Prediction Discrete Dynamic Model

Abstract: Forest ecosystem is the most important terrestrial ecosystem type of species diversity in the world. The protection and sustainable use of forest ecological diversity is of great significance to forest protection and sustainable management. In order to maintain biodiversity, the traditional concept of forest resources management must be changed. In recent years, the mining and application of big data have become the frontier content of international ecological diversity and macroecology research. By establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The conversation of this exploration paper centres around the drivers of deforestation and woods corruption, strategy, and the board ways to deal with address the issue of deforestation and woodland debasement. The concentrate in [7] shows the assurance and feasible utilization of woodland biological variety is of extraordinary importance to backwoods security and supportable administration. The writing survey features that deforestation is basically determined by horticultural extension, logging, mining, foundation advancement, and urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…The conversation of this exploration paper centres around the drivers of deforestation and woods corruption, strategy, and the board ways to deal with address the issue of deforestation and woodland debasement. The concentrate in [7] shows the assurance and feasible utilization of woodland biological variety is of extraordinary importance to backwoods security and supportable administration. The writing survey features that deforestation is basically determined by horticultural extension, logging, mining, foundation advancement, and urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…Tian [13] proposed a new prediction method for short-term wind speed based on local mean decomposition (LMD) and combined kernel function least squares support vector machine (LSSVM), and the results show that the proposed prediction method has higher prediction accuracy and can reflect the laws of wind speed correctly. Li et al [14] constructed a WebGIS scheme of forest information system and open-source network geographic information system oriented to spatial information field and supported OGC and used the grey model to predict the development trend. e results showed that the method realized the double growth of forest area and forest volume, and the forest coverage rate reached a new level.…”
Section: Introductionmentioning
confidence: 99%